INFLUENCE OF DEMOGRAPHIC FACTORS ON SELF-ESTEEM OF HEARING-IMPAIRED ADOLESCENTS - Abid Masood Khan,; Muhammad Imran Nazir,; Rabail Iftikhar Cheema, (JIE, 2025)
Self-esteem plays a vital role in the emotional and psychological development of adolescents, particularly those with hearing impairments who face additional social and communicative challenges. The study attempted to explore the influence of demographic factors on the self-esteem level of hearing-impaired adolescents. The study was descriptive in nature, and a survey method was used to collect data. The population of the study was hearing-impaired adolescents studying in government special education institutions in Faisalabad Division of Punjab Province. A sample of N=100 hearing-impaired adolescents was selected through a convenience sampling technique. The age range of the children was 13 to 19 years old. The Rosenberg self-esteem scale (1965) was used as tool of study for the collection of data. The collected data were analysed through Statistical Package for Social Sciences (SPSS) software by using the Independent Sample t-test and One-Way ANOVA. The study found that the living arrangements of hearing-impaired adolescents influenced their level of self-esteem, but gender, family type, age, and birth order had no influence on the self-esteem level of hearing-impaired adolescents.